2021
DOI: 10.1111/obr.13200
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue macrophages as a therapeutic target in obesity‐associated diseases

Abstract: Summary Obesity is an increasing problem in developed and developing countries. Individuals with obesity have a higher risk of several diseases, such as cardiovascular disease, increased risk of insulin resistance, type 2 diabetes, infertility, degenerative disorders, and also certain types of cancer. Adipose tissue (AT) is considered an extremely active endocrine organ, and the expansion of AT is accompanied by the infiltration of different types of immune cells, which induces a state of low‐grade, chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 161 publications
(299 reference statements)
1
20
0
1
Order By: Relevance
“…For chronic systemic low-grade inflammation in type 2 diabetes, insulin resistance is to blame [16], which also promotes microinflammation [6] and macroinflammation [7], leading to the aggravation of cardiovascular complications [17]. We found that insulin resistance progressed gradually with the development of the disease, resulting in increased aortic IL-6 and IL-1β levels, which suggested that insulin resistance promoted aortic inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…For chronic systemic low-grade inflammation in type 2 diabetes, insulin resistance is to blame [16], which also promotes microinflammation [6] and macroinflammation [7], leading to the aggravation of cardiovascular complications [17]. We found that insulin resistance progressed gradually with the development of the disease, resulting in increased aortic IL-6 and IL-1β levels, which suggested that insulin resistance promoted aortic inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…M1 type ATMs are considered pro-inflammatory phenotypes in adipose tissue, and M2 type ATMs are considered anti-inflammatory phenotypes, but ATMs cannot be mechanically recognized in practice. A growing number of studies have shown that ATMs have multiple origins, with their functions spanning pure pro- or anti-inflammatory effects, and they are highly plastic and can achieve phenotypic transformation under specific circumstances, which can be therapeutic targets in the future ( 75 , 76 ).…”
Section: Atms and Obesitymentioning
confidence: 99%
“…Specifically, a high-fat diet (HFD) in mice induces an inflammatory phenotype in microglia, the resident immune cells of the CNS (11,12). Additionally, HFD or other CNS pro-inflammatory events increase trafficking of peripheral immune cells into the brain (13)(14)(15), further promoting neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%